Neuroprotective effect of damaurone D in a C. elegans model of Parkinson's disease. (16th March 2021) - Lee, Seung Hyun; Han, Young Taek; Cha, Dong Seok
Highlights: Damaurone D alleviates MPP + -induced dopaminergic neurodegeneration. Damaurone D improves behavior impairment induced by MPP + . Damaurone D attenuates aggregation and expression of α-synuclein. Abstract: In this study, we evaluated the protective effects of damaurone D (DaD), a dihydropyranoaurone compound, on dopaminergic (DA) neurodegeneration in Caenorhabditis elegans . The results showed that DaD treatment could successfully increase the survival rate of the worms under MPP + exposure. Additionally, DaD protected against the MPP + -induced neurodegeneration in all eight DA neurons of the worms. Similarly, diminished DA neuronal damage was observed in the DaD-fed transgenic mutant overexpressing tyrosine hydroxylase. In addition, the corresponding behavioral impairment induced by MPP + was strongly improved in the DaD treated worms, implying DaD has protective properties for DA neuronal function. Then, we further investigated the effect of DaD on α-synuclein aggregation, a key pathogenesis of Parkinson's disease (PD). In this study, DaD reduced the fluorescence signals of transgenic mutants that carried YFP-fused α-synuclein. A similar reduction in expressions of α-synuclein was observed by Western blot. Interestingly, our result from the dot-blot assay demonstrated that the formation of oligomers was significantly attenuated by the DaD treatment. Furthermore, DaD improved the abnormal fat storage and shortened lifespan of the animals with the same genetic background which supports the beneficial action of DaD on the α-synuclein-induced DA neurodegeneration. These results demonstrate that DaD could protect against both chemical- and genetic-induced DA neurodegeneration possibly through the modulation of oxidative stress, DA metabolism, and α-synuclein toxicity. Based on our present findings, we suggest that DaD might have a potential therapeutic role in Parkinson's disease.